Empowering Dasawisma Group in Nagari Lasi through Cultivation and Utilization of Family Medicinal Plants - Tika Afriani; Azimatur Rahmi; Yulia Ningsih (LP2M INSURI Ponorogo, 2026)
While many empowerment programs focus solely on planting, this study integrates cultivation with the creation of innovative herbal products. The program involved six selected Dasawisma groups (Anggrek, Melati, and Mawar) in Nagari Lasi, Agam Regency. A Community-Based Research approach was conducted over eight months (July–December 2023), utilizing a structured questionnaire to measure knowledge and direct observation for skill assessment. Knowledge regarding TOGA cultivation and processing increased significantly by 82%. The groups successfully transformed harvests into innovative commercial products, including